Potensi sukuk hijau dalam menjawab tantangan lingkungan hidup di Kota Malang - Putri, Marsela Rosiana (Maliki Interdisciplinary Journal, 2024)
Green Sukuk issued by the Government of Indonesia both in global and domestic offerings has goals in two aspects, namely economic growth and the environment. Research that uses the normative-empirical juridical method is an assessment of the product of laws and regulations with a historical approach to legislation. Through the fact of product issuance from the enactment of a law, namely Green Sukuk based on POJK No. 60 of 2017 in responding to environmental challenges. Green Sukuk demonstrates its commitment to environmental preservation through the development projects it has implemented. Aspects of sustainable environmental insight are the main points in the issuance of Green Sukuk. This supports government programs in efforts to mitigate the risk of environmental damage due to climate change, global warming, and greenhouse gas emissions. The City Government of Malang can cooperate with companies engaged in the five financing sectors resulting from the Green Sukuk offering, in this case, PLN is a company that has a correlation with waste and waste management as an alternative to the use of fossil fuels. In addition, through Green Sukuk, the government receives funding from offering assets to investors globally and domestically, so it is not only environmental aspects but also economic aspects Keywords: Green Sukuk; Environment; Sharia Capital Market.